Elementary knowledge about epilepsy among the patients, their family, and common people (Faculty of Medicine Universitas Indonesia, 2003)
It is assumed that health education has been done and health information has been given through health service institutions and mass media, but it seems that the patients as well as common people have insufficient knowledge about epilepsy. Interviews had been carried out upon 127 epilepsy patients in out patient clinic Dr. Kariadi Hospital Semarang, 95 patients’ family, and 95 common people to explore their knowledge on the main disturbed organ, etiology, symptoms and signs, and trigger factors of repeating seizure in epilepsy. The respondents’ answers were recorded verbatim, and analyzed by matching to the right answers according to references. Bad andinsufficient knowledge on the main organ disturbed in epilepsy, etiology, symptoms and signs, and trigger factors for repeated seizure was founded among the epilepsy patients, their family, and common people. There were no significant differences of the level of knowledge among the three groups of respondents. The patients’ knowledge was the worst, compared to the others. The level of education of the respondents did not influence their level of knowledge. In conclusion, this study reflects an insufficientcommunication between doctors and the patients in the healthservice institution, and an insufficient public health education about epilepsy received by the patients’ family and common people. (Med J Indones 2003; 12: 29-39) Keywords: epilepsy, knowledge, patients, common people